Pandangan Sikap Intovert dalam Filsafat Stoikisme - Muhammad Fazril Ubaidillah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss introverted attitudes in the view of stoicism philosophy. This study uses a qualitative approach by applying the method of library research (library research). The formal object of this study is the stoicism of Marcus Aurelius, while the material object is introverted behavior. The results and discussion in this study indicate that Marcus Aurelius' stoicism philosophy emphasizes that humans must